Evaluasi Pelayanan Rehabilitasi Sosial Lanjut Usia Terlantar pada Unit Rehabilitasi Sosial Pucang Gading Semarang - Taufiq R Ghazali; Reni Windiani; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
This research was conducted to explain the results of an evaluation of the services provided by the Centerfor Social Rehabilitation Pucang Gading Semarang. Hall is structurally under Social Service of Central JavaProvince. Through this Center, patients with neglected elderly earn a decent living and get adequate treatment.In order to explain the evaluation of services that have been implemented Social Rehabilitation CenterPucang Gading semarang we used mixed methods (the methods of qualitative and quantitative methods). Subjectsin this study were Social Service of Central Java province, officials and staff of the Social Rehabilitation CenterPucang Gading Semarang, families of neglected elderlys and the public. The method of data collection was throughinterviews, observation, research documents .The results showed that the Social Rehabilitation Center Pucang Gading Semarang to perform itsobligations to provide services to people with neglected elderly, through several stages of raids stages, stages oftreatment and care, stages of return to the family. In the raid was quite intensive stages in the implementation andadministration of the districts of Central Java Province. At the stage of care and service is very good, the hallprovides the tools and infrastructure needed to support the mental development of the people and also always givemedical measures deemed necessary and providing drugs to support the health of the patient. At the stage of thereturn to the family is less effective because the general public still can not accept the presence of people withneglected elderly.